Predictive value of Hounsfield units and vertebral bone quality on cage subsidence in oblique lateral interbody fusion with bilateral posterior fixation - Chaoshuo Liu; Zixi Zhang; Wenzhao Li; Jialin Zhang; Bing Wang; Xinzhan Mao; Shun Yang; Tao Tu; Yichao Xiao; Cancan Wang; Zhenbin Wang (Journal of Orthopaedic Surgery and Research)
Abstract Background Cage subsidence (CS) is a significant complication following oblique lateral interbody fusion combined with bilateral pedicle screw fixation (OLIF-BPSF) in patients with spinal degenerative diseases (SDDs). Identifying reliable predictors of CS is crucial for optimizing surgical outcomes. Methods This retrospective cohort study included 314 SDD patients who underwent OLIF-BPSF between July 2019 and July 2023. Preoperative Hounsfield unit (HU) values and vertebral bone quality (VBQ) scores were measured. Statistical analyses included correlation matrices, Kaplan–Meier survival analysis, Cox proportional hazards models, restricted cubic splines, and receiver operating characteristic (ROC) curve analysis. Sensitivity analyses were performed to ensure robustness. Results CS occurred in 13.38% of patients. Lower global (HR: 0.97, 95% CI: 0.97–0.99) and segmental (HR: 0.97, 95% CI: 0.95–0.98) HU values were significantly associated with higher CS incidence, whereas higher global (HR: 1.67, 95% CI: 1.29–2.16) and segmental (HR: 1.68, 95% CI: 1.30–2.17) VBQ scores were also significantly associated with increased CS risk. A nonlinear relationship was observed between the VBQ score and CS, with CS incidence significantly increasing when the global VBQ score was ≥ 2.67 or the segmental VBQ score was ≥ 2.49. ROC analysis demonstrated good predictive performance for HU values and VBQ scores, with segmental HU values showing superior incremental predictive value (AUC: 0.82). The findings remained consistent across various sensitivity analyses. Conclusion HU values and VBQ scores independently predict CS in SDD patients undergoing OLIF-BPSF. Incorporating these metrics into preoperative assessments may enhance risk stratification and guide personalized surgical planning.